Amputation Rates, Mortality, and Pre-operative Comorbidities in Patients Revascularised for Intermittent Claudication or Critical Limb Ischaemia: A Population Based Study. (October 2017) - Baubeta Fridh, E.; Andersson, M.; Thuresson, M.; Sigvant, B.; Kragsterman, B.; Johansson, S.; Hasvold, P.; Falkenberg, M.; Nordanstig, J.
Abstract : Objectives: The aims of this population based study were to describe mid- to long-term amputation risk, cumulative incidence of death or amputation, and differences in pre-operative comorbidities in patients revascularised for lower limb peripheral artery disease (PAD). Methods: This was an observational cohort study. Data from the Swedish National Quality Registry for Vascular Surgery (Swedvasc) were combined with mandatory national health care registries and patient medical records. All patients who underwent revascularisation in Sweden between May 2008 and May 2013 for intermittent claudication (IC) or critical limb ischaemia (CLI), aged 50 years and older, were identified through the Swedvasc database. The mandatory national health care registries and medical records provided data on comorbidities, mortality, and major amputations. Results: A total of 16, 889 patients with PAD (IC, n = 6272; CLI, n = 10, 617) were studied. The incidence of amputations in IC patients was 0.4% (range 0.3%–0.5%) per year. Among CLI patients, the amputation rate during the first 6 months following revascularisation was 12.0% (95% CI 11.3–12.6). Thereafter, the incidence declined to approximately 2% per year. The cumulative combined incidence of death or amputation 3 years after revascularisation was 12.9% (95% CI 12.0–13.9) in IC patients and 48.8% (95% CI 47.7–49.8) in CLI patients. Among CLI patients, compared with IC patients, the prevalence of diabetes, ischaemic stroke, heart failure, and atrial fibrillation was approximately doubled and renal failure was nearly tripled, even after age standardisation. Conclusion: The risk of amputation is particularly high during the first 6 months following revascularisation for CLI. IC patients have a benign course in terms of limb loss. Mortality in both IC and CLI patients is substantial. Revascularised CLI patients have different comorbidities from IC patients.